KAJIAN PEMANFAATAN MATRAS BAMBU PADA PERBAIKAN NILAI CALIFORNIA BEARING RATIO (CBR) TANAH LEMPUNG - Aazokhi Waruwu; Memotani ZEGA; Debby ENDRIANI; Rika Deni SUSANTI (FROPIL (Forum Profesional Teknik Sipil), 2021)
Clay soil has low bearing capacity, stability, and CBR (California Bearing Ratio). Subgrade with low CBR need reinforcement to improve mechanical properties and increase bearing capacity when compacting and spreading soil with heavy equipment and when the vehicle load is working on the road surface. Bamboo material has the potential to be used as reinforcement for clay soil. This study aims to determine the effect of woven and non-woven bamboo mat reinforcement and the effect of the number of layers of reinforcement on the CBR value. Reinforcement of bamboo mats is distinguished by 3 and 5 layers of woven and non-woven types with the number of strokes on the CBR specimen as many as 25-blow and 56-blow. The CBR test was conducted on unreinforced and reinforced clay. The CBR value of soil reinforced with non-woven bamboo mats was obtained at 4.4-5.06%, while the CBR value for soils with reinforced woven bamboo mats was 4.56-5.30%. The arrangement of the woven type bamboo mats is closer and tied to each other, making it more sturdy and stable in accepting the load. The number of layers of reinforcement with closer vertical spacing results in a higher CBR value than the number of layers of reinforcement that are less. Closer vertical spacing can expand the pressure contact area, so that the load that can be carried is higher. Woven type bamboo mats with more layers were found to have good performance in increasing the CBR value of subgrade for road construction.